Life Experiences of Black Student-Athletes in Revenue-Producing Sports: A Descriptive Empirical Analysis - Sellers, Robert M.; Kuperminc, Gabriel P.; Waddell, Andrea S. (My University, 1991)
Recent NCAA reform (Propositions 48 and 42) have made imperative a better understanding of the social and psychological factor affecting black student-athletes in revenue-producing sports. This study focused on the college experience of black student-athletes at 42 NCAA Division I schools in comparison to white student-athletes and other black college students in four areas: demographic and academic background; college life experience; mental health; and social support. Black student-athletes differed from both comparison groups across all four topic areas. Results of the comparison were discissed, and policy recommendations were presented. The present study examined data from a national representative sample of full-time undergraduate student-athletes at Division I institutions commissioned by the Presidents Commission of the NCAA. Forty-two of the 291 Division I institutions for 1987-1988 were randomly selected to participate. lnstitutions were relatively evenly distributed across the NCAA's geographic districts and regions and were representative on a variety of indicators of institutional and student body characteristics, as well as sports history and involvement. A total of 5123 student-athletes and students was sampled. This study focused on three subgroups within the sample: black student-athletes participating in revenue-producing sports n=847); white student-athletes participating in revenue-producing sports (n=1161); and a random sample of black students who were not members of an athletic team (n=511). The participants' informed consent was obtained. Questionnaires were administered in group of four or five students, with at least one data collector present. They had four categories: demographic and academic background, college life experiences, mental health status, and social support. Results suggested that black student-athletes enter the university with very different educational and socio-cultural backgrounds than both white student-athletes and other black students. Black student-athletes have significantly lower family income and less educated parents. Greater differences erre found when comparing black student-athletes with other black students than with white student-athletes. Black and white student-athletes do not differ in the importance they ascribe to earning a degree, their satisfaction in their relationship with coaches, and their overall satisfaction with life.
Keywords: race; demographics; Division I; academic performance; well-being; social support